2013
DOI: 10.1159/000355014
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Renal Responsiveness to Atrial Natriuretic Peptide in Experimental Nephrotic Syndrome by Albumin Infusion

Abstract: Background: The natriuretic/diuretic response to atrial natriuretic peptide (ANP), an important regulator of water and Na+ balance, is markedly attenuated in nephrotic syndrome (NS). It has been suggested that the diminished renal responsiveness to ANP may contribute to the pathogenesis of salt retention and edema formation in NS. However, the mechanisms underlying the renal hyporesponsiveness to ANP remain largely unknown. Methods: The acute effects of exogenous infusion of ANP (5 µg/kg + 10 µg/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…In NS, resistance to serum ANP is an observation in experimental animals and humans [ 17 , 18 ], these studies showed that ANP levels were frequently elevated in INS children than in healthy or remission children. Restoration of renal receptiveness to ANP in animal models of NS by albumin infusion indicates that renal hypo-responsiveness to ANP is a reversible functional condition rather than permanent cellular damage [ 19 ]. Moreover, Cataliotti et al observed increased plasma ANP concentration that frequently correlated with the edema severity [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In NS, resistance to serum ANP is an observation in experimental animals and humans [ 17 , 18 ], these studies showed that ANP levels were frequently elevated in INS children than in healthy or remission children. Restoration of renal receptiveness to ANP in animal models of NS by albumin infusion indicates that renal hypo-responsiveness to ANP is a reversible functional condition rather than permanent cellular damage [ 19 ]. Moreover, Cataliotti et al observed increased plasma ANP concentration that frequently correlated with the edema severity [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid is a common treatment means, and most children can be cured, but there are also some children who are insensitive to glucocorticoid, so the disease relapses and the healing is delayed, finally developing into refractory nephropathy, affecting the healthy growth and development of children [5,6]. Factors affecting the prognosis of NS in children include the long-term repeated edema.…”
Section: Discussionmentioning
confidence: 99%
“…The striated muscle dissolved because of the intramuscular injection of glycerol, the myoglobin and other potentially toxic intracellular components released into the systemic circulation. The mechanisms of glycerol-induced myoglobinuric ARF are renal vasoconstriction and congestion, ischaemia, and myoglobin induced cytotoxicity [2,3]. Moreover, there is growing evidence indicating that the reactive oxygen species (ROS) plays an important role in the pathogenesis of myoglobinuric ARF, oxidative stress would participate in the tubular necrosis favoring lipid peroxidation of cellular membranes [1,4].…”
Section: Introductionmentioning
confidence: 99%